ELECTRONIC DISCLOSURE PADA PERUSAHAAN TELEKOMUNIKASI ASIA PASIFIK DI NEW YORK STOCK EXCHANGE (NYSE) - Kesumajuda, Fiqi Ardiansyah (Jurnal Akuntansi dan Keuangan Indonesia, 2006)
The aims o f the research is to measure the level o f disclosure by creating index with the purpose o f evaluating electronic disclosure practicing in Asean com panies, especially fo r emiten in telecommunication industry that listed in NYSE. Electronic disclosure that form electronic disclosure rankings between emiten show that there is low disclosure fo r electronic disclosure and also low disclosure fo r level o f company’s qualitative information especially information about corporate gov ernance, corporate responsibility and ethical code o f the companies. However, the disclosure about background o f the company, financial data, media center, informa tion acceptability and annual report show relatively high index